CURRICULUM DESIGN FOR SPECIAL CONDITIONS BASED ON ISLAMIC VALUES: Study at Senior High School Al-Hikmah Boarding School Batu - Hidayatullah, Muhammad Fahmi; Firdausi, Muhamad Anwar; Hanief, Muhammad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Covid-19 is a way for each educational institution to improve quality, processes, as well as facilities and infrastructure. The epidemic indirectly demands the education institution for adaptive and innovative new life accompanied by the development of information technology. The Ministry of Education and Culture has issued a curriculum policy for special conditions during the pandemic based on the circular regulation of the Minister of Education and Culture Number 719 of 2020. In addition, the issue of freedom to study in primary and secondary education institutions has emerged since 2019. Through the locus of Senior High School al-Hikmah Boarding School Batu, the researchers explored the data regarding the design of an independent curriculum based on Islamic values implemented since 2019. The curriculum has relevance to the Covid-19 special conditions curriculum and can be used as a model for the Covid-19 curriculum based on Islamic values. The research approach used is descriptive qualitative. While, the type of research is a case study with in-depth interview data collection, participatory observation, and documentation. It used an interactive data analysis through data collection, data presentation, data reduction, and conclusions. The results of this study indicate that the independent curriculum of al-Hikmah Boarding School Batu has relevance to the link and match-based special conditions curriculum. In addition, the independent curriculum contributes to shaping the learners’ attitudes based on spiritual strength, nationalism, and mental leadership.